2021
DOI: 10.1111/aji.13472
|View full text |Cite
|
Sign up to set email alerts
|

Can altered colostrum miRNA expression profile after cesarean delivery be a risk factor for autoimmune diseases?

Abstract: Problem The cesarean section (CS) rate has increased significantly in North America, Western Europe, and Latin America. However, it has been reported that the incidence of inflammatory and autoimmune diseases such as asthma and type 1 diabetes increased in parallel with CS in these countries. Our aim was to investigate the expression level of miRNAs associated with inflammatory response and autoimmune diseases in colostrum samples and contribute to elucidating the role of CS in the pathogenesis of immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
1
1
Order By: Relevance
“… 35 Furthermore, a study indicated a significant upregulation of 17 miRNAs in the colostrum of mothers who had undergone CS. 36 In conjunction with our study’s findings, it is evident that the mode of delivery can influence miRNA levels in cord blood.…”
Section: Discussionsupporting
confidence: 86%
“… 35 Furthermore, a study indicated a significant upregulation of 17 miRNAs in the colostrum of mothers who had undergone CS. 36 In conjunction with our study’s findings, it is evident that the mode of delivery can influence miRNA levels in cord blood.…”
Section: Discussionsupporting
confidence: 86%
“…Although very little is known about the impacts of delivery mode on human milk miRNA composition, one small prior study of preterm infants (n = 31) reported statistically significant correlations between a select number of gestational age-associated milk EVP miRNAs and delivery mode in preterm infants but did not investigate this in infants delivered at term [28]. A previous study of colostrum also reported that delivery via cesarean section was associated with two of the same miRNAs (miR-16-5p and miR-30e-5p) that were associated with the delivery mode in our study, although in the opposite direction [47]. To the best of our knowledge, our study is the first to examine the association between the delivery mode and miRNA levels in mature human milk from individuals who delivered at term or post-term.…”
Section: Discussioncontrasting
confidence: 73%
“…The current literature landscape investigates the relationship between CS delivery and autoimmune disorders. With current studies citing associations between CS delivery and inflammatory disorders, asthma, eczema, and connective tissue disorders 17 20 . To note, Yerlikaya et al 20 highlighted a significant alteration in the expression of various miRNA sequences in the microbiota of CS patients experiencing inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%